Cr-free Ni/MgO catalysts for hydrogenation of furfural - Jiménez-Gómez, Carmen Pilar; Cecilia-Buenestado, Juan Antonio; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (My University, 2018)
In the last century, the industrial development and the increase of the world population have caused the depletion of fossil reserves. This fact together with others factors have led to the search of alternative. Biomass is emerging as a widely available source to produce energy and, excluding fossil fuels, is the only source that can provide liquid fuels and chemicals. Lignocellulose is formed by cellulose, hemicellulose, lignin and other extractable components. In the case of hemicellulose, its hydrolysis leads to the formation of xylans and pentosans, which after dehydration can give rise to furfural. The high interest for furfural is attributed to its chemical structure, which provide high reactivity, making it potentially interesting for the synthesis of a vast variety of high value-added chemicals. Two of these important chemicals are furfuryl alcohol (FOL) and 2-methylfuran (MF), can be synthesized through hydrogenation of furfural, either in liquid or vapor phase. FOL is mainly used for the production of thermostatic resins, intermediates in the manufacture of lysines, vitamin C and dispersing agents. Meanwhile, MF is used in the synthesis of pesticides, in the pharmaceutical or perfume industries. Industrially, copper chromite catalyst is used, although the toxicity associated to the presence of chromium species has prompted the search of Cr-free catalysts. Therefore, much attention is being paid to the development of more sustainable and environmentally friendly catalysts, among them, catalytic systems based on Cu or Ni have demonstrated to be active and selective towards the formation of FOL and MF. The dispersion of metalspecies and their interaction with the support are key parameters that affect the catalytic activity and stabilityof catalysts. The use of metal oxides as supports can allow to obtain highly active and stable catalytic systems, and the electronic density of metal sites can be modified. The present work is aimed at the synthesis by Ni/MgO catalysts and the evaluation of their catalytic performance in the gas phase hydrogenation of furfural, at atmospheric pressure. x-Ni_MgO catalysts have been tested in the furfural hydrogenation, attaining the full furfural conversion with the 0.20-Ni_MgO catalyst, after 5 h of TOS, at 190 °C, by feeding a 5% furfural solution in cyclopentyl methyl ether, at a constant flow of hydrogen of 10 ml min-1. In all cases, catalysts are highly selective to furan. The analysis of the influence of the reaction temperature has revealed the existence of a volcano distribution, attaining the best catalytic performance at 190 °C. However, all catalysts suffer a progressive deactivation with TOS, by deposition of reactants and product.
Keywords: Biomasa; Catalizadores metálicos; Furfural; Biomass; Hydrogenation; Metal catalyst; Nickel